Modification of Total Alkaline-Silica Method for Naming Volcanic Rocks - Benyamin; Muhammad Burhannudinnur; Suryo Prakoso; Mohamad Salsabila; Dwi Kurnianto (Journal of Earth Energy Science, Engineering, and Technology, 2025)
The use of the Total Alkaline-Silica (TAS) method from Maitre (2002) has been a very important object for scientists involved in the world of volcanology for years. Much literature shows that the use of this method is generally acceptable and well used for naming volcanic rocks, although for certain volcanic rocks such as lamprophyres, for example, there are still limitations in the use of this method. The TAS method requires the results of rock chemical analysis in the form of total Alkaline content which is the sum of Sodium Oxide (Na2O) and Potassium Oxide (K2O) on one side and total Silica content (SiO2) on the other side, which means that without the availability of chemical analysis results for both components, the TAS method cannot be used or the method can still be used by modifying the components of the chemical analysis results with other components, in this case it will be tried to replace it with the magnitude of various data from logging. The purpose of this study depends on the availability of logging data in the area to be studied in various variations such as Nuclear, Electrical and Acoustic Logs with various crossplots from the available logs. The results of the various crossplots are then validated using core rock data that has been named using petrographic analysis based on the naming of volcanic rocks using the classification commonly used in the discipline of volcanology.